2020
DOI: 10.1177/2042018820958329
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune thyroid disease and type 1 diabetes mellitus: same pathogenesis; new perspective?

Abstract: Autoimmune thyroid disease (AITD) and type 1 diabetes mellitus (T1DM) are two common autoimmune diseases that can occur concomitantly. In general, patients with diabetes have a high risk of AITD. It has been proposed that a complex genetic basis together with multiple nongenetic factors make a variable contribution to the pathogenesis of T1DM and AITD. In this paper, we summarize current knowledge in the field regarding potential pathogenic factors of T1DM and AITD, including human leukocyte antigen, autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 252 publications
2
27
1
Order By: Relevance
“…The study was conducted to assess the correlation between the occurrence of AITD and the development of DKD. AITD and DM1 are common autoimmune diseases [ 17 ]. AITD occurs in 17–30% of DM1 patients, and approximately 25% of children with DM1 have antithyroid antibodies (ATA) at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted to assess the correlation between the occurrence of AITD and the development of DKD. AITD and DM1 are common autoimmune diseases [ 17 ]. AITD occurs in 17–30% of DM1 patients, and approximately 25% of children with DM1 have antithyroid antibodies (ATA) at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…T lymphocytes in ltrate the glands, then subsequent development of various degrees of thyroid dysfunction. 7 Thyroid hormones T4 and T3 were produced by a glycosylated transmembrane protein named thyroid peroxidase, which is distributed in the apical part of follicular thyroid cells. 13 Metabolomics techniques have shown that people who develop diabetes have different levels of certain lipids when compared with people who remain non-diabetic.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune thyroid disease (AITD) and T1DM are two common autoimmune diseases and can occur concomitantly. 7 Many studies have demonstrated that changes in serum thyroid hormone parameters are associated with diabetes. A study concluded that thyroid hormone parameters seemed to re ect the effects of a prolonged period of catabolism, DKA, or both.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of AITD involves cellular and humoral autoimmune mechanisms against the thyroid gland. T lymphocytes in ltrate the glands, then subsequent development of various degrees of thyroid dysfunction [22] . Thyroid hormones T4 and T3 were produced by a glycosylated transmembrane protein named thyroid peroxidase, which is distributed in the apical part of follicular thyroid cells [23] .Metabolomics techniques have shown that people who develop diabetes have different levels of certain lipids when compared with people who remain non-diabetic [24] .In addition, thyroid dysfunction can lead to metabolic disorders.…”
Section: 62±342 Years)mentioning
confidence: 99%